A high density urban temperature network deployed in several cities of Eurasian Arctic. (6th July 2018) - Konstantinov, Pavel; Varentsov, Mikhail; Esau, Igor
Abstract: Dense meteorological networks are needed to advance understanding of urban climatology in the northern polar region where global warming is rapid and amplified. High quality and density urban temperature datasets are required to monitor thawing processes in urban soils, properly assess and project climatic trends in human comfort, air quality and weather extremes. This study presents an Urban Heat Island Arctic Research Campaign (UHIARC) observational network, which has been deployed in several mid-sized cities (Salekhard, Vorkuta, Nadym, Novy Urengoy) of the Eurasian Arctic region in the winter of 2016–2017. The network comprises an array of air temperature loggers and one automatic weather station in each of these four cities. The UHIARC observations revealed strong warm temperature anomalies in all four cities. Such persistent temperature anomalies are frequently referred to as urban heat islands (UHIs). The mean wintertime magnitude of these temperature anomalies (the UHI intensity) was found to be between 0.8 K and 1.4 K. Extreme UHI intensities up to 7 K were observed during cold anticyclonic weather conditions. Such a strong mediation of cold temperature spells by UHI might induce considerable socio-economic and environmental impacts in the cities. The UHIARC dataset is available for further analysis fromhttp://urbanreanalysis.ru/uhiarc.html .